Cannabinoids for Behavioral Symptoms in Dementia: An Overview - Broers, Barbara; Bianchi, Federica (Pharmacopsychiatry, 2024)
Dementia, with loss of memory, cognitive abilities, and independent daily functioning, is increasing worldwide, related to an aging population. Currently, there is no curative treatment for dementia. Treatment of the frequently occurring behavioral and psychological symptoms of dementia (BPSD) is partially effective and associated with significant side effects. Cannabinoids are lipophilic molecules acting on the CB1 end CB2 receptors, essential for main biological processes such as sleep, appetite, memory, and pain. Cannabinoids might have a positive impact on amyloid formation in Alzheimer’s disease, the main form of dementia, and on BPSD symptoms. Most knowledge currently concerns delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD). In the context of dementia and BPSD, THC might be beneficial for associated spasticity and possible pain or lack of appetite and CBD probably works better on sleep, agitation, and anxiety. This overview of prospective clinical studies and randomized clinical trials, published between 2005 and April 2023, using cannabinoids for BPSD suggests that older studies using low-dose oral synthetic THC showed no positive results. Still, more recent studies using THC/CBD-based oral medication at higher doses show promising results and are feasible and safe in this elderly polymedicated population. Several RCTs are ongoing and planned worldwide, and we hope other trials will follow to establish clinical efficiency and optimal dosing, as well as other outcomes such as deprescribing other medications and facilitation of care. We suggest that researchers also address the more sociological aspects of prescribing cannabinoids for dementia and BPSD in their specific context.
Keywords: dementia; medical cannabis; dronabiol; BPSD; cannabinoids